Fossil seeds of Sideroxylon L. (Sapotaceae) from the Neogene of Europe and their relationships to extant species in Macaronesia and West Asia - Edoardo Martinetto; Steven R. Manchester; Rubén Barone; Ulf Swenson (Earth History and Biodiversity)
Sideroxylon mascatense is a shrub or small tree of the high mountains of western Asia and is sister to S. spinosum L. of NW Africa, the latter being the source plant of the famous Argan Oil. Based on distinctive features of seed morphology, we demonstrate that closely related plants were native in the Neogene of central Europe. The most similar fossils occur in the Neogene of Italy and are assigned to Sideroxylon ruminatiusculum Martinetto, Manchester, R.Barone et Swenson sp. nov. Other European fossil carpological remains, formerly assigned to Sapindoidea globosa (R.Ludw.) Kirchh., agree with Sideroxylon mascatense in the external morphology and anatomy of the ruminate seeds, but are larger. We therefore propose the new combination Sideroxylon globosum (R.Ludw.) Martinetto, Manchester, R.Barone et Swenson comb. nov. In the type locality of Salzhausen (Germany, Miocene) Sideroxylon globosum co-occurs with similar, though smaller and less ruminate seeds, formerly assigned to Sapindoidea Kirchh., but here reclassified as Sideroxylon margaritiferum (R.Ludw.) Martinetto, Manchester, R.Barone et Swenson comb. nov. The European fossil seeds of Sideroxylon were produced by plants that grew under the wet palaeoclimates of the Neogene. The proposed systematic relationship suggests that members of this group adapted to increasing aridity around the Mediterranean and western Asia during the late Cenozoic and persisted there until recent times. The latest known European occurrence is represented by Late Pliocene (ca. 3 Ma) fossils from Central Italy. Despite strong similarities between the fossils and Sideroxylon mascatense, other extant species of the genus, such as the Canary Islands and Madeira species, differ in these seed characters and do not seem to be closely related to the studied European fossils.